Flexible Flat‐Panel Display Designs with Gate Driver Circuits Integrated within the Pixel Area. Issue 1 (June 2014) - Yoshida, Hidefumi; Tanaka, Kohei; Murata, Mitsuhiro; Noma, Takeshi; Nishiyama, Takayuki; Yonebayashi, Ryo; Kanehiro, Masayuki; Nakanishi, Yohei
Abstract We have developed a new stylish TFT‐LCD. We located gate‐driver monolithic circuits in the pixel area. As there are no electronic circuits in the frame area, we can realize a narrow border and round corners or a multi‐concave shape, and the frame shape can be easily revised.